Solve for n f=3/2*(n-62)

Math
f=32⋅(n-62)
Rewrite the equation as 32⋅(n-62)=f.
32⋅(n-62)=f
Multiply both sides of the equation by 23.
23⋅32⋅(n-62)=23f
Simplify both sides of the equation.
Tap for more steps…
Simplify 23⋅32⋅(n-62).
Tap for more steps…
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
23⋅32⋅(n-62)=23f
Rewrite the expression.
13⋅3⋅(n-62)=23f
13⋅3⋅(n-62)=23f
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
13⋅3⋅(n-62)=23f
Rewrite the expression.
1⋅(n-62)=23f
1⋅(n-62)=23f
Multiply n-62 by 1.
n-62=23f
n-62=23f
Combine 23 and f.
n-62=2f3
n-62=2f3
Add 62 to both sides of the equation.
n=2f3+62
Solve for n f=3/2*(n-62)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top